2013
DOI: 10.1021/jp402039g
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar Morphology of Derivatives of Poly(3-alkylthiophene)s by Solvent Vapor Annealing: Effects of Conformational Transition and Conjugate Length

Abstract: A fibrillar morphology was obtained, compared to the featherless pristine films, via solvent annealing the films of a series of derivatives of poly(3-alkylthiophene)s (P3ATs): poly(3-dodecylthiophene) (P3DDT), poly(3,3'''-didodecyl-quaterthiophene) (PQT12), and poly(2,5-bis(3-dodecylthiophen-2-yl)thieno[3,2-b]thiophene) (pBTTT12). Among the solvents used, including dichloromethane, chloroform, tetrahydrofuran, and carbon disulfide (CS2), CS2 was the best to induce fibril formation because its solubility parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Thus, a smaller solubility parameter difference between solvent and solute determining a good solubility is important to satisfy the premise of ordered aggregation and enhance performances. Liu et al and Wang et al reported that with closer solubility parameters of solvent to polymer, the crystallinity and/or fibrillar morphology in films became improved [79,173]. Meanwhile, with the similar solubility parameters, a larger polarity of solvent led to a drop of carrier mobility.…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a smaller solubility parameter difference between solvent and solute determining a good solubility is important to satisfy the premise of ordered aggregation and enhance performances. Liu et al and Wang et al reported that with closer solubility parameters of solvent to polymer, the crystallinity and/or fibrillar morphology in films became improved [79,173]. Meanwhile, with the similar solubility parameters, a larger polarity of solvent led to a drop of carrier mobility.…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
“…It brings difficulty to the crystallization of chains during casting or post-annealing. Especially for conjugated polymers with larger conjugation lengths, Wang et al reported that (1) the critical nucleation vapor pressure was higher due to the higher critical vapor pressure for rod-to-coil transition during solvation and (2) the fibril density was reduced partly due to the slower motion of units during aggregation, which were the results of the larger conjugation lengths and enhanced rigidity for polymers ( Figure 7) [79]. Therefore, tuning the crystallization and morphology of conjugated polymers is challenging due to their conjugated molecular structures.…”
Section: Structural Differences Between Conjugated Polymers and Fleximentioning
confidence: 99%
See 3 more Smart Citations